2011
DOI: 10.1002/macp.201000653
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Chemical Composition Distribution of LLDPE Using Interactive Liquid Chromatography

Abstract: It is demonstrated that copolymers of ethylene with higher 1‐olefins can be separated using bare silica gel as the stationary phase and a gradient of ethylene glycol monobutyl ether and 1,2,4‐trichlorobenzene as the mobile phase at 160 °C. The separation of ethylene 1‐hexene copolymers according to their composition is confirmed by linking the chromatographic separation to infrared spectroscopy. Using well‐characterised model fractions from temperature rising elution fractionation or solvent/non‐solvent fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A detailed discussion of some major developments in the field has recently been presented by Pasch et al 18 and Monrabal 17 . Different experimental protocols have been developed that make use of the different modes of interaction chromatography including liquid chromatography at critical conditions (LCCC) 73,74 and various solvent gradient systems 75–78 . As two representative examples, the chemical composition separation of ethylene‐vinyl acetate copolymers (EVA) and the tacticity separation of polypropylene (PP) shall be presented.…”
Section: Advanced Fractionation Methodsmentioning
confidence: 99%
“…A detailed discussion of some major developments in the field has recently been presented by Pasch et al 18 and Monrabal 17 . Different experimental protocols have been developed that make use of the different modes of interaction chromatography including liquid chromatography at critical conditions (LCCC) 73,74 and various solvent gradient systems 75–78 . As two representative examples, the chemical composition separation of ethylene‐vinyl acetate copolymers (EVA) and the tacticity separation of polypropylene (PP) shall be presented.…”
Section: Advanced Fractionation Methodsmentioning
confidence: 99%
“…The precipitation enabled the separation of isotactic PP from linear PE [60,64] as well as the separation of ethylene-propylene copolymers [66,67] according to their chemical composition. Separations of ethylene-butene and ethylene-hexene copolymers were evaluated in this sorbent/solvent system by Dolle et al [68] which showed that PE with low molar mass (o20 kg/mol) is soluble in EGMBE [64] and thus may elute without retention from the column.…”
Section: Chromatographic System Based On the Precipitation-dissolutiomentioning
confidence: 99%
“…Separations of ethylene–butene and ethylene–hexene copolymers were evaluated in this sorbent/solvent system by Dolle et al . 68 which showed that PE with low molar mass (<20 kg/mol) is soluble in EGMBE 64 and thus may elute without retention from the column.…”
Section: Molecular Characterization Of Polyolefinsmentioning
confidence: 99%
“…This chromatographic approach was also applied to the separation of EPC [55] and for the separation of various polyolefins with regard to the chemical composition of the components [154].…”
Section: Ht-hplc Based On Precipitation-redissolutionmentioning
confidence: 99%